Pronomina Persona Bahasa Melayu Ambon di Wilayah Tutur Kota Ambon - Erniati Erniati (UNDAS: Jurnal Hasil Penelitian Bahasa dan Sastra, 2020)
Penelitian ini bertujuan mendeskripsikan bentuk-bentuk pronomina persona bahasa Melayu Ambon. Jenis penelitian ini bersifat deskriptif kualitatif mengkaji fenomena kebahasaan yang secara objektif. Data dalam penelitian berupa data lisan yang bersumber dari tindak komunikasi masyarakat Kota Ambon dan sekitarnya yang terdiri atas semua rentang usia, yang menggunakan bahasa Melayu Ambon. Data dikumpulkan menggunakan metode observasi melalui teknik rekam dan catat. Data yang telah diklasifikasi dianalisis secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa pronomina bahasa Melayu Ambon terdiri atas pronomina persona pertama tunggal dan jamak, pronomina persona kedua tunggal dan jamak, pronomina persona ketiga tunggal dan jamak, dan pronomina persona leksem kekerabatan.The objective of this study is to describe the types of personal pronouns in the Ambonese Malay language. This research applies the qualitative descriptive method to analyze the language phenomenon objectively. The research data are oral data taken from communication between the people in Ambon City and its surroundings, which consists of all ages of the Ambonese Malay language speaker.  The data are collected using the observation method, recording, and writing technique. The analysis of selected data is using a descriptive qualitative method. The results show that there are several pronouns of the Ambonese Malay language. They are first-singular personal pronouns, and first-plural personal pronouns; second-singular personal pronouns, and second-plural personal pronouns; third-singular personal pronoun, and third-plural personal pronouns; kinship lexeme personal pronouns.